2018
DOI: 10.1002/hed.25433
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of textural indices extracted from pretherapeutic 18‐F FDG‐PET/CT in head and neck squamous cell carcinoma

Abstract: Background This study aimed at assessing the prognostic value of textural indices extracted from 18F‐fluorodeoxyglucose positron‐emission tomography (FDG‐PET)/CT in a large cohort of patients with head and neck squamous cell carcinomas (HNSCC) of any anatomic subsite and staging. Methods Consecutive patients with HNSCC referred for a pretreatment FDG‐PET/CT were retrospectively included and followed up for a minimum of 2 years. Standardized uptake value, metabolic tumor volume (MTV), and textural indices were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
49
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(52 citation statements)
references
References 45 publications
(113 reference statements)
0
49
0
Order By: Relevance
“…Evaluating intra-tumoral heterogeneity with textural indices may help thoroughly classifying patients between different risk subgroups. It would be particularly useful in HNSCC, conjointly with usual prognostic factors, to select patients with poor prognosis who would require intensified therapy [31].…”
Section: Discussionmentioning
confidence: 99%
“…Evaluating intra-tumoral heterogeneity with textural indices may help thoroughly classifying patients between different risk subgroups. It would be particularly useful in HNSCC, conjointly with usual prognostic factors, to select patients with poor prognosis who would require intensified therapy [31].…”
Section: Discussionmentioning
confidence: 99%
“…Textural analysis on pre-RT FDG-PET/CT, already recognized as a prognostic factor for survival (40), could be an interesting approach to predict HNSCC local recurrence sites. Beaumont et al showed that 15 parameters extracted from a voxel to voxel analysis, combining radiomics and spatial location, allowed better prediction of local failure than a regional analysis, with a median area under the receiver-operating curve of 0.71 (41).…”
Section: In the Ntp Group)mentioning
confidence: 99%
“…In this study 32/284 (11%) patients with larynx cancer were included. The imaging acquisition method was the FDG PET/CT, and the discriminant features were metabolic tumor volume, correlation, entropy, energy, and coarseness [5]. Ulrich, E. et al evaluated the utility of radiomic feature analysis from 18F-fluorothymidine positron emission tomography (FLT PET) obtained at baseline in prediction of treatment response in patients with head and neck cancer.…”
Section: Radiomics and Laryngeal Cancermentioning
confidence: 99%
“…Extracted image features include measurements of intensity, shape, and texture [4]. Specifically, texture analysis represents a set of tools to improve characterization of tumor heterogeneity consisting of extracting texture indices from different imaging modalities as CT, MRI, or fluorodeoxyglucose (FDG) PET/CT [5]. These imaging modalities allow clinicians to extract a large amount of quantitative features whose subsequent analysis and selection can be incorporated in clinical decision-making.…”
Section: Introductionmentioning
confidence: 99%